2017
DOI: 10.18632/genesandcancer.155
|View full text |Cite
|
Sign up to set email alerts
|

JNK-signaling: A multiplexing hub in programmed cell death

Abstract: Jun N-terminal kinases or JNKs have been shown to be involved in a wide array of signaling events underlying tumorigenesis and tumor progression. Through its interaction with a diverse set of signaling proteins and adaptors, JNKs regulate cell proliferation, invasive migration, therapy resistance, and programmed cell death. JNKs have been shown to play a role in apoptotic as well as non-apoptotic programmed cell death mechanisms including those of necroptosis, ferroptosis, pyroptosis, and autophagy. Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
189
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(212 citation statements)
references
References 113 publications
10
189
0
Order By: Relevance
“…Systemic FAK14 did not induce any obvious deficits in mice and is well tolerated in clinical trials for cancer. JNK might be a better target than FAK because it can be pro-apoptotic (Dhanasekaran and Reddy 2017) but systemic JNK inhibition remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic FAK14 did not induce any obvious deficits in mice and is well tolerated in clinical trials for cancer. JNK might be a better target than FAK because it can be pro-apoptotic (Dhanasekaran and Reddy 2017) but systemic JNK inhibition remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…JNK/AP1 pathway is a key regulator of many cellular events, including cell death. [36][37][38][39][40][41][42][43] JNK/AP1 has pro-or anti-apoptotic functions, depending on cell type, nature of the death stimulus, duration of its activation and the activity of other signaling pathways. Studies have shown that in response to chronic stress, JNK/ AP1 activates the apoptosis pathway in order to eliminate the stressed cells.…”
Section: Discussionmentioning
confidence: 99%
“…JNK promotes apoptosis by several signalling pathways that were characterised in different cell experimental models. It is unlikely that all of the observed JNK's pro-apoptotic effects are present in all of the cells at the same time [120]. However, it is important to be aware of the JNK's ability to modulate apoptosis at different levels.…”
Section: Examples Of Signalling Molecules That Regulate Crosstalk Amomentioning
confidence: 99%
“…Activation of tumour necrosis factor receptor superfamily (e.g. TLRs or TNFαR) or DNA damage can trigger necroptosis by activation of the Complex I-IIa-IIbphosphorylated pseudokinase mixed lineage kinase domain-like protein (MLKL) signalling pathway; the final steps are (a) RIP3-dependent phosphorylation of MITO proteins PGAM5 and Drp-1 (increasing MITO ROS production); (b) insertion of phosphorylated MLKL into the MITO membrane with the cumulative effects of increased MITO membrane permeability, loss of membrane potential, decreased ATP and increased ROS production [120,[167][168][169]; and (c) phosphorylated MLKL's translocation to the plasma membrane and activation of Ca 2+ influx through plasma membrane channels with concomitant plasma membrane breakdown [169]. Increased cytosolic ROS production inactivates MAP kinase phosphatase 1, enabling sustained activation of phosphorylated JNK; phosphorylated JNK promotes necroptosis by (a) stimulating MLKL phosphorylation and by (b) promoting cytochrome c release from MITO via activation of BID [170,171].…”
Section: Examples Of Signalling Molecules That Regulate Crosstalk Amomentioning
confidence: 99%